2012
DOI: 10.1101/cshperspect.a006551
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Parallels between Neural and Vascular Development

Abstract: The human central nervous system (CNS) features a network of 400 miles of blood vessels that receives .20% of the body's cardiac output and uses most of its blood glucose. Many human diseases, including stroke, retinopathy, and cancer, are associated with the biology of CNS blood vessels. These vessels originate from extrinsic cell populations, including endothelial cells and pericytes that colonize the CNS and interact with glia and neurons to establish the blood -brain barrier and control cerebrovascular exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(58 citation statements)
references
References 99 publications
0
58
0
Order By: Relevance
“…Neurons and vessels share similar signaling pathways that mediate differentiation, maturity, and migration. They also have similar parallel branching structures [72] . Therefore, neurogenesis and angiogenesis may infl uence each other after cerebral ischemia.…”
Section: Ischemiamentioning
confidence: 92%
“…Neurons and vessels share similar signaling pathways that mediate differentiation, maturity, and migration. They also have similar parallel branching structures [72] . Therefore, neurogenesis and angiogenesis may infl uence each other after cerebral ischemia.…”
Section: Ischemiamentioning
confidence: 92%
“…Furthermore, cerebral vasculature also crucially participates in brain neural network formation and brain function in both the developing brain and adult brain. It has been shown that the structural generation and functional activity between cerebral vasculature and neurons are tightly linked together (Carmeliet and Tessier-Lavigne, 2005; Eichmann and Thomas, 2013). …”
Section: The Intrinsic Capability Of Brain Self-repair In Stroke Recomentioning
confidence: 99%
“…Embryonic vascular formation involves vasculogenesis (the growth of new vessels from angioblasts), angiogenesis (the sprouting of new blood vessels from pre-existing vessels via endothelial migration and extracellular matrix remodelling), and vessel maturation and stabilization (Eichmann and Thomas, 2013;Wacker and Gerhardt, 2011). The formation of specialized features, such as those in the blood-brain barrier, may also ensue.…”
Section: Lpa Signalling During Vascular Developmentmentioning
confidence: 99%